Colonel James Bowie. - Holmer, Paul L. (1995)
Keywords: dept.lib; faculty_collection; sabbatical_report

The Pharos: The Ancient Lighthouse of Alexandria, Egypt. - Clarie, Thomas C. (1990)
Keywords: dept.lib; faculty_collection; sabbatical_report

Statistical Analysis of the Holdings, Circulation and Acquisitions of the Buley Library Book Collection. - Kobus, Julia (1988)
Keywords: dept.lib; faculty_collection; sabbatical_report

A Compendium of Faculty Research and Scholarship - Clarie, Thomas C. (Southern Connecticut State University, 1997)
Keywords: Bibliography; Connecticut; dept.lib; faculty_collection

LC MARVEL: A Guide - Cavanagh, Shirley B. (1995)
Keywords: Southern Connecticut State University; Internet; dept.lib

A Comprehensive, Annotated Bibliography on Mahatma Gandhi - Pandiri, Ananda M. (Bibliographies and indexes in world history ; no. 42, 1995)
Keywords: Bibliography; Gandhi, Mahatma, 1869-1948; dept.lib; faculty_collection

Buley Library Connecticut Room Collection; Holdings List - Hilton C Buley Library; Clarie, Tom; Bennett, Claire (Southern Connecticut State University. Hilton C. Buley Library. Reference Department, 1986)
Keywords: Bibliography; Catalogs; Library catalogs; Connecticut; dept.lib; faculty_collection

Occult/Paranormal Bibliography: An Annotated List of Books Published in English, 1976 Through 1981 - Clarie, Thomas C. (Scarecrow Press, 1984)
English-language books published or reissued between 1976-1981. Arranged alphabetically by authors. Asterisks indicate excellence. Author, title, and subject indexes.
Keywords: Bibliography; Bibliography; Parapsychology; Occultism; dept.lib; faculty_collection

New Haven in 1884 - Shumway, Floyd M.; Hegel, Richard (Journal of the New Haven Colony Historical Society ; v. 30, no. 2, winter 1984, 1984)
Keywords: History; New Haven (Conn.); dept.lib; faculty_collection

New Haven: An Illustrated History - Shumway, Floyd M.; Hegel, Richard; New Haven Colony Historical Society (Windsor Publications, 1981)
Keywords: Description and travel; History; New Haven (Conn.); New Haven (Conn.); dept.lib; faculty_collection

Occult Bibliography: An Annotated List of Books Published in English, 1971 Through 1975 - Clarie, Thomas C. (Scarecrow Press, 1978)
Keywords: Bibliography; Bibliography; Parapsychology; Occultism; dept.lib; faculty_collection

Finis E. Engleman: A Biographical Sketch - Hegel, Richard (Department of Instructional Services, Southern Connecticut State College, 1975)
Keywords: Engleman, Finis Ewing, 1895-; dept.lib; faculty_collection

Nineteenth-Century Historians of New Haven. - Hegel, Richard (Archon Books, 1972)
Keywords: 19th century; New Haven (Conn.); Connecticut; Historiography; History; New Haven; dept.lib; faculty_collection

NHSTC: The Growing Community College for the Greater New Haven Area - Buley, Hilton C. (INFO, 1959)
Keywords: Community colleges; Connecticut; History; dept.lib; faculty_collection